Upaya Guru Pendidikan Agama Islam Dalam Menyikapi Dampak Penggunaan Gadget Pada Siswa Kelas VII Di SMP PGRI 1 Kasembon - Romeli, Muhamad; Rozaq, Abd. (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2022)
The use of gadgets (HP) in class VII students, the problems raised in this study are 1. How to use gadgets (HP) in class VII SMP PGRI 1 Kasembon. 2. How are PAI Teachers' Efforts in Responding to the Use of Gadgets (HP) in Class VII Students of SMP PGRI 1 Kasembon. 3. What is the impact of using gadgets (HP) on seventh-grade students of SMP PGRI 1 Kasembon. 2. Efforts Applied by PAI Teachers in Responding to the Use of Gadgets (HP) in Class VII Students of SMP PGRI 1 Kasembon. relevant future studies. This research is afield research with a qualitative approach. A qualitative approach is a series of activities or processes for disclosing something that is not yet known by using the methods of interviews, observation, documentation methods, data analysis, and data validity. Research results in 1. The Impact of Using Gadgets (HP) on Class VII-A Junior High School Students PGRI 1 Kasembon. 2. Cooperation with all parties including school principals, PAI teachers, and parents of students in responding to the impact of using gadgets (HP). Research conclusions, among others. 1. Policy From Principals and PAI Teachers Regarding the Use of Gadgets (HP) for Class VII Students at SMP PGRI 1 Kasembon. 2. Giving Assignments By PAI Teachers To Students Which In Their Work To Be Supervised By Parents.3. The Impact of Using Gadgets (HP) That Are Difficult to Control Among Students.